Sustainability science and technology : an introduction (CRC Press, 2014)
"This book builds a bridge between sustainability science and engineering. It provides the latest information on sustainability issues and solutions by discussing them from basic concepts to scientific consensus to technical solutions. It identifies and addresses the major issues related to sustainability with an environmental science perspective, and presents the connections and interactions between science and technology through a very practical approach and easy understanding. "-- Provided by publisher.
Keywords: Sustainability.; Sustainable development -- Technological innovations.; Environmental responsibility.; elektronické knihy; electronic books